(untitled) (Research, Society and Development, 2022)
Objective: To investigate dietary intake, obstetric, clinical, anthropometric, glycemic and lifestyle variables in pregnant women with Gestational Diabetes Mellitus (GDM). Methods: This is a descriptive, quantitative study, developed from March to August of 2018, at the Hospital das Clínicas from UFPE. Sociodemographic, anthropometric variables, lifestyle, glycemic control and gestational feeding were studied. For statistical analysis, the Mann-Whitney, Kruskal-Wallis and Shapiro-Wilk tests were performed, with a error margin of 5%. Results: 65 pregnant women aged> 19 years were assessed. Pre-gestational overweight occurred in 73.8% of the sample, while during the gestational period it increased to 84.6%; fasting glycemia was higher in pregnant women with overweight and in those who were sedentary. The consumption of glycemic risk foods was positively associated with pre-gestational BMI. The practice of physical activity was performed by 9.2% of the group, without associations with other lifestyle parameters. Conclusion: Pregnant women with GDM presented overweight and elevated fasting glycemia in the majority, an association was observed between the consumption of risk foods with overweight and the mostly of the sample was sedentary.